Exploring Residents’ Willingness to Pay for Renewable Energy Supply: Evidences from an Italian Case Study - Grilli, Gianluca; Balest, Jessica; Garegnani, Giulia; Paletto, Alessandro (Journal of Environmental Accounting and Management, 2026)
The present study offers a contingent valuation application to explore residents ´ willingness to pay for renewable energy, in a case study in the Italian Alps. Data originated from onsite personal interviews and were analyzed with a Tobit model. Results show that respondents are willing to pay, on average, 5.1€ per month for a 100% of renewable energy supply, corresponding approximately to a 13% increase in the energy bill. Among the factors positively affecting the answers, the personal knowledge about renewable energy plays a key role in predicting WTP, as well as income and the personal perception of future possible development of hydropower plants. On the other hand, age and number of household components negatively affect WTP.